Herzog & de Meuron. Fondazione Feltrinelli a Milano - Volpe, Andrea (Firenze Architettura, 2021)
Evoking the figure of the ancient bastion of the Spanish walls, of the great monumental architectures and of the houses with balustrades that characterise the city of the master which they met in Zurich, Herzog & de Meuron formulate, by subtraction, perhaps the most complete and radical homage to Rossi and to that period of European architectural culture, underlining – surprisingly – its essential nature.